Penerimaan dan Pengetahuan Mahasiswa tentang Assessment for Learning - Mumpuni, Kistantia Elok; Ramli, Murni (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
Assessment for learning (AfL) is considering the results of evaluation to rearrange better learning activities. One of assessments, formative assessment, is an information of development of students achievemnet in the learning activities. In addition, it is very usefull for redesign the next learning strategies to increase students capability, especially for teachers. So that, ability to conduct AfL is necessary for prospective teachers. This research is aimed to describe the approvement and understanding of prospective teacher to AfL. Survey, by using questionnare, is used in this research. Study objects were 59 students of Pendidikan Biologi Sebelas Maret University who enrolled in fourth semester. The data were analyzed qualitatively. The results showed that the most of students are realized the functions of assessment in the learning. Arround 67,8% of students stated that study plan can be changed based on the results of formative assessment. Meanwhile, 73,7% of students prefered written examination compared to the oral one and all of students are agree that every evaluation have to performe a feedback. Moreover, they are 69,5% and 74,6% of students decided on written and oral feedback respectively and the oral feedback is given by the teacher or lecturer. Then, all of students agree that feedback has some benefits to rise learning qualities. To conclude, the survey showed that students have approvement and understanding to the functions of AfL, kinds of assessment and feedback, and the subject of feedback. Prospective teacher needs more practice to use AfL and its application to reach the goals of learning.